Leadership In Ethiopian Public Universities; Capacity And Challenges - Gebremedhin, Mulugeta Fisseha; Gupta, Bhawna (Gyan Management Journal, 2023)
Literature is evidently characterized by a plethora of definitions and correspondingly the actual practice of leadership is characterized by complexity. This applies to the leadership of higher education too. But it is the public universities that has to contend more with competing needs and expectations of diverse stakeholders. This paper thus examines leadership capacity and challenges in Ethiopian public universities. To this end a mixed approach was utilized. The result shows that leaders of the study area lacks the ability to manage complexity and change, and a knowledge of the technical and quantitative skills necessary , and the managing of diversity, the ability to work as a team were also lacking. Furthermore, Leaders have a propensity to concentrate on known issues and known solutions. The Study also suggested that leaders with a full range of traits on personal, organizational, performance and social mastery are needed to lead and fully engage in the process of achieving sustainable performance outcomes. Empowerment must play a role in developing ‘the best qualities’ of our people. Finally, providing a training link between all levels of the hierarchy were deemed vital for leadership excellence to flourish